In vitro drug sensitivity profile ofstxand eaeA positive Escherichia coli from diarrhoeic calves in Kashmir valley - KAWOOSA, S S; SAMANTA, I; WANI, S A (The Indian Journal of Animal Sciences, 2011)
A total of44 E. coli isolates, from 300 diarrhoeic calves, carrying stx (stxJ, stx2 and their variants), eaeA and hlyA genes and maintained by the Division were selected for this study. Antibiotic sensitivity pattern of isolates tested revealed highest resistance to oxyteracycline (51.51 %) and nalidixic acid (51.51%), followed by co-trimoxazole (42.42%), ofloxacin (21.21%), enrofolxacin (18.18%) and chloramphenicol (18.18%). Among the multidrug resistant STEC isolates, 06, 077, 086 and 0171 serogroups showed resistance to six of nine antimicrobials tested in the present study.Â